Molecular detection and genetic diversity of Dientamoeba fragilis and Enterocytozoon bieneusi in fecal samples submitted for routine parasitological examination - Bertozzo, Thainá [UNESP]; David, Érica; Oliveira-Arbex, Ana; Guimarães, Semíramis [UNESP] (Wolters Kluwer, 2021)
Objective: To detect Dientamoeba (D.) fragilis and Enterocytozoon (E.) bieneusi and to assess their genetic characteristics in stool samples submitted for routine examination in a clinical laboratory in Southeastern Brazil. Methods: In this survey, 348 stool samples from female and male individuals with age ranging from 0 to ≥55 years were analyzed by PCR amplifying and sequencing based on the small subunit ribosomal RNA (SSU rRNA) gene of D. fragilis and the internal transcribed spacer of E. bieneusi. Results: D. fragilis and E. bieneusi isolates were observed in 2.29% (8/348) and 4.59% (16/348) of the samples, respectively. These parasites were detected in stool samples from individuals of both genders, including young children under nine until adults over 55 years old. No statistically significant differences were found. All D. fragilis isolates were classified as genotype 1 and E. bieneusi isolates included genotypes D (n=15) and A (n=1). Conclusions: The findings provide relevant findings on occurrence and genetic diversity of D. fragilis and E. bieneusi, pointing to the need for the diagnosis of these parasites in routine examinations in clinical laboratories. In addition to sensitive diagnostic methods, it is mandatory that these parasites be considered relevant for physicians and laboratory staff.
Keywords: Clinical laboratory; Dientamoeba fragilis; Enterocytozoon bieneusi; Genotyping; PCR